HUBUNGAN KEMITRAAN SEBAGAI STRATEGI PENGEMBANGAN USAHA - Julissar An-Naf (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2006)
Partnership is a cooperation among enterprises in business sectors: government, private, including cooperative sectors, in which each actor gains benefit from the scheme. Technically, partner relationship can be carried out through nucleus-plasma relationship, sub-contracting, trading, franchise/licensing, sub-distributing, and other forms. Partner relationship among large, medium, and small business units is considered as the most suitable form in accord with the ideas of Chapter 33rd of the 1945 Basic Constitution of the Republic of Indonesia as elaborated by Law of Republic of Indonesia Number 9, Year 1995 concerning Small Business or well known as the Partnership Law. By the above partnership pattern caul relationship some aggregate amount of added values or profit margins from the business system can simultaneously and proportionally or properly be distributed to the actors in respective business linkage and cycles hence improves and betters the terms of trade among the business.